1996
DOI: 10.1111/j.1095-8649.1996.tb01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine, osmoregulatory, respiratory and haematological parameters in flounder exposed to the water soluble fraction of crude oil

Abstract: Flounders Pleuronectes flesus with an implanted vascular catheter were exposed to a 50% dilution of the water soluble fraction (WSF) of Omani crude oil (c. 6 ppm total aromatic hydrocarbons) and serial blood samples taken to determine their endocrine status (cortisol, catecholamines and thyroid hormones) and the resultant and/or causal physiological (haematological, ionoregulatory and respiratory) disturbances. This resulted in a progressive increase in plasma cortisol concentrations from 3 h onwards (rising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…Hemolysis may impair the oxygen capture and gas exchange capacity of these animals, as well as interfere in the acid-base equilibrium (Bloom & Brandt, 2008). Similar findings have been reported for Prochilodus lineatus exposed to the water-soluble fraction of diesel oil (Simonato et al, 2008) and for flounder (Pleuronectes flesus) after exposure to the water-soluble fraction of crude oil (Alkindi et al, 1996). According to Duarte et al (2010), the hydrocarbons in petroleum seriously impair oxygen transport, since they are known to alter the permeability of erythrocytes with a strong hemolytic effect.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hemolysis may impair the oxygen capture and gas exchange capacity of these animals, as well as interfere in the acid-base equilibrium (Bloom & Brandt, 2008). Similar findings have been reported for Prochilodus lineatus exposed to the water-soluble fraction of diesel oil (Simonato et al, 2008) and for flounder (Pleuronectes flesus) after exposure to the water-soluble fraction of crude oil (Alkindi et al, 1996). According to Duarte et al (2010), the hydrocarbons in petroleum seriously impair oxygen transport, since they are known to alter the permeability of erythrocytes with a strong hemolytic effect.…”
Section: Discussionsupporting
confidence: 72%
“…Changes in hematological parameters have already been found in fish exposed to different types of petroleum and derivatives (Davison et al, 1993;Alkindi et al, 1996;Duarte et al, 2010) but it is evident that the hematological responses may vary among species and different pollutants, and additional information such as ion concentrations and osmolarity are necessary to define a relationship between the pollutant and the variations observed.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have observed that crude oil alters plasma constituents, including plasma enzymes, electrolytes and amino acids. Findings in this study contradicted the observation of Alkindi et al (1996), who showed that water soluble fraction of Omani crude oil did not affect plasma There was no significant difference between treated groups and control.…”
Section: Discussioncontrasting
confidence: 56%
“…1974). Alkindi et al (1996), showed that water soluble fraction of Omani crude oil resulted in a progressive increase in plasma cortisol concentrations from 3 h onwards (rising from 18 to 51 ng ml −1 after 48-h exposure), increased plasma glucose concentration, did not affect plasma osmolality, sodium and chloride concentration but caused decrease in plasma potassium concentration in Flounders Pleuronectesflesus.…”
Section: Introductionmentioning
confidence: 99%
“…Values represent the means and SE (n"5/treatment). Statistically signi"cant di!erences between exposed "sh and control "sh are *P(0.05; **P(0.02; ***P(0.01; ****P(0.001. approach (Anderson et al, 1974;Alkindi et al, 1996;EHC, 1996). According to previous studies (Anderson et al, 1974;Dunlap and Beckman, 1988), these WSFs contain polar and low-molecular-mass compounds, namely, aromatic hydrocarbons included in two toxicologically relevant groups: BTEX compounds (benzene, toluene, ethyl benzene, and xylene isomers) and small PAHs, in particular naphthalenes.…”
Section: Figmentioning
confidence: 98%